Promoting an Appreciation for Diversity Through Reading Literary Works to Prevent Radicalism - Yunidar Yunidar; Gusti Ketut Alit Suputra; Anjar Kusuma Dewi (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This study aims to identify the factors of prejudice that can lead to radicalization among elementary school students and to improve understanding of the values of diversity and tolerance through academic literacy. This study was conducted in elementary schools in Palu City involving 500 students who were divided into two groups: experimental and control. The research method used was descriptive research with a quasi-experimental design, where both groups were given pre- and post-tests to measure the increase in attitudes of respect and tolerance. Data were collected through test instruments that measured students' moral attitudes towards diversity and radicalization, while data analysis techniques used descriptive statistics and hypothesis testing. The results showed that the experimental group that participated in the